Football Disasters and Pilgrimage: Commemoration through Religious and Non-Religious Ritual and Materiality - Eade, John (Religions, 2024)
Although the relationship between religion and football has gained considerable interest during the last twenty years, scant attention has been paid to the relationship between pilgrimage and football. This paper seeks to advance the study of this relationship through an exploration of collective memory about football disasters that throws fresh light on central themes within pilgrimage studies—pilgrimage as both a journey to a sacred place and the performance of diverse rituals at such places. The paper explores, in particular, the ways in which three different tragedies involving English football clubs have been commemorated through journeys to and ritual performance at places seen as sacred to those involved in commemoration—football stadiums and urban spaces, and cathedrals and pilgrimage shrines in England, Germany and Italy. Through this analysis, we seek to show how the commemoration of football disaster is linked to pilgrimage as a process where people seek healing and reconciliation through the public performance of rituals that link the local to the global.